Understanding the Socially Responsible Investment Choices of Individual Investors in India - Meenakshi Rani, Ankit Garg, Surbhi Agarwal, Nagavani Kaggallu, Mayuri Tayal, Ajay Kumar Varshney, Himanshu Sharma (Journal of Informatics Education and Research, 2024)
The study examines the attitudes, understanding, and preparedness of Indian retail investors to address environmental, social, and governance (ESG) issues. In order to identify important demographic characteristics, awareness levels, attitudes, willingness, and particular impediments that affect their Socially responsible investing (SRI) decisions, the study also discusses the difficulties Indian investors encounter when evaluating SRI solutions. A tailored survey and descriptive statistics were used to collect and evaluate data, and the theory of planned behavior (TPB) and binary logistic regression offered insights on the reasons behind SRI engagement. The results suggest that while investors are interested in SRI and understand the importance of ESG, there is a lack of general information regarding SRI. There are still many obstacles to overcome, such as the absence of tax advantages, the belief that returns will be smaller, a lack of liquidity, ignorance, and worries about possible returns. According to the logistic regression analysis, demographic characteristics had less of an impact on SRI decision-making than having a clear investing objective and being knowledgeable about SR/ESG funds and indexes. The paper highlights the need to raise SRI awareness among Indian investors and has practical ramifications for lawmakers, asset management companies, government agencies, and ethical fund managers. It suggests that while issuers should give accurate information on SRI options and the risks and advantages involved, regulators should concentrate on SRI education. By examining SRI awareness, attitudes, willingness, and obstacles among Indian individual investors—areas that haven't received much attention in previous research—this study adds something special.